PEMBELAJARAN BAHASA ARAB (Kajian Tentang Prinsip, Sistem, Aspek dan Metode Mengajarkannya) - Lubis, Ali Asrun (AIN Padangsidimpuan, 2013)
AbstraksiPeople would recognize a school good for its Arabic subject. It is studied for communication and qiraat skills. Here, students study it actively and productively. It means that students might able to speak, write, listen to and read.There are two systems to study Arabic; they are union system and division system. Union system takes united systems. The division system takes divided systems on any sciences. Accordingly, students might have reading, writing, speaking and listening skills for both systems.Moreover, there are Arabic teaching methodologies; lecturing, question and answer discussion, socio-drama, drilling, and recitation to reach those skills. Finally, teachers’ understanding towards students’ ages, time use, stationeries, project tools and teachers’ preparation for the subjects are supported principles, systems, aspects, and teaching methodology.Kata Kunci : Pembelajaran, Bahasa Arab